The regional level as boundary organization? An analysis of climate change adaptation governance in Norway. Issue 54 (December 2015) - Dannevig, Halvor; Aall, Carlo
Highlights: We find that regional level coordination of adaptation in Norway consists mostly of boundary work. Despite centralized governance system, regional authorities coordinate adaptation differently. Regional level coordination effort creates a hybrid management space for adaptation. Knowledge for adaptation could be improved by involving municipal users in knowledge production. Abstract: This paper investigates how a requirement for regional government to coordinate adaptation planning has been interpreted and implemented. Using the theory of boundary organization applied to a multi-level context, and using four counties in Western Norway as a case, the paper develops a framework for assessing how regional level governance actors can support local level implementation of climate change adaptation through boundary work. Even though adaptation is not treated as a salient issue in most of the municipalities studied, regional level coordination efforts are creating a hybrid management space that aids mediation between local knowledge and expert adaptation knowledge. They thus hold the potential for better local level adaptation planning.